An Investigation of the Antiproliferative Effect of Rhododendron luteum Extract on Cervical Cancer (HeLa) Cells via Nrf2 Signaling Pathway. (28th May 2022) - Turan, Ibrahim; Demir, Selim; Yaman, Serap Ozer; Canbolat, Deniz; Mentese, Ahmet; Aliyazicioglu, Yuksel
Abstract: The aim of the present study was to investigate the role of Rhododendron luteum extract (RLE) in the induction of Nrf2‑related oxidative stress and endoplasmic reticulum (ER) stress in human cervical cancer (HeLa) cells. The antiproliferative effect of RLE on HeLa and fibroblast cells was determined using the MTT assay. The effects of RLE on the cell cycle, apoptosis, and production of reactive oxygen species (ROS) in HeLa cells were evaluated using fluorescent probes. The mRNA expression levels of Nrf2 [and its targets glutamate-cysteine ligase catalytic subunit (GCLC), and glucose-6-phosphate dehydrogenase (G6PD)], and C/EBP homologous protein (CHOP, an ER stress marker were determined using reverse transcription‑quantitative polymerase chain reaction (RT-PCR). The results demonstrated that RLE exhibited a selective cytotoxic effect (2.9-fold) on HeLa cells compared to fibroblast cells. RLE arrested the cell cycle at the S phase, and induced apoptosis, ER stress, and ROS formation. In addition, RLE significantly suppressed the expression levels of Nrf2, GCLC and G6PD (0.65, 0.69, and 0.54-fold, respectively) and increased the expression of CHOP (4.48-fold) in HeLa cells at 72 h of treatment ( p  < 0.05). These results show that the antiproliferative effect of RLE occurs through the Nrf2 and ER stress pathways, and the results should now be supported by further in vivo studies.